Cultural Event, Social Media, And Local Community Empowerment (A Case Study Of The 2024 Jember Fashion Carnaval Campaign On Instagram, TikTok, And YouTube) - Salsabila Nada Azzahra (Universitas Negeri Yogyakarta, 2025)
This study explores the role of social media in cultural events and the empowerment of local communities, focusing on the 2024 Jember Fashion Carnaval (JFC) social media campaign on Instagram, TikTok, and YouTube. With the increasing influence of social media in modern communication and promotion, this research investigates how these platforms are utilized by JFC to broaden its audience reach, engage with a global audience, and promote local culture. Known for its spectacular fashion parade and innovative art presentations, the event leverages social media as a strategic tool for promotion and community empowerment. Using qualitative methods, including interviews and content analysis, this study assesses the effectiveness of the campaign in developing local skills, fostering cultural exchange, and creating economic opportunities for the Jember community. Additionally, the research evaluates the impact of digital platforms in enhancing public participation and increasing the event's international visibility. This study provides valuable insights into optimizing social media strategies for promoting cultural heritage and empowering local communities in the digital age. Keywords: Social Media, Jember Fashion Carnaval, Local Community Empowerment, Digital Campaign, Local Culture